Classification of Reserves for Business Accounting Purposes - І. GRINENKO (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
Due to accumulation of reserves and their appropriate accounting and recording, business enterprises are allowed to increase assets, quickly respond on the occurrence of unpredicted costs and liabilities, and comply with the principle of business continuity. The classification of reserves as objects of accounting is the key to the sound recording and enclosure of information about them in the financial statements of a business enterprise. The research objective is to analyze and sum up classification criteria and types of reserves, and to develop recommendations on improvements in the classification of reserves for business accounting purposes.             Approaches of Ukrainian authors to the classification of business reserves as an object of accounting are investigated. It is revealed that the researchers propose a wide range of the classification criteria. The most widespread classification criteria are compulsory accumulation, accumulation sources, and accumulation purpose. But the proposed criteria are diverse to the extent that the system approach to the recognition, valuation and recording of reserves cannot be applicable. The author’s approach to the classification of reserves by various criteria is proposed as a way to resolve the problems of constructing an accounting system for reserves as accounting objects and provide an appropriate information support for business enterprises. The types of reserves and classification criteria proposed by the author on the basis of the research can give multifaceted characteristics of the studied object, and can be used as a framework for accounting and recording of transactions related with accumulation and utilization of reserves.